Evaluation of a topical formulation of eprinomectin against Anopheles arabiensis when administered to Zebu cattle (Bos indicus) under field conditions. (December 2016) - Lozano-Fuentes, Saul; Kading, Rebekah; Hartman, Daniel; Okoth, Edward; Githaka, Naftaly; Nene, Vishvanath; Poché, Richard
Abstract Background Although vector control strategies, such as insecticide-treated bed nets (ITNs) and indoor residual spraying (IRS) have been effective in Kenya the transmission of malaria continues to afflict western Kenya. This residual transmission is driven in part byAnopheles arabiensis, known for its opportunistic blood feeding behaviour and propensity to feed outdoors. The objective of this research was to evaluate the efficacy of the drug eprinomectin at reducing malaria vector density when applied to cattle (Bos indicus ), the primary source of blood forAn. arabiensis, under field conditions. Methods A pilot study was carried out in the Samia District of western Kenya from September to October of 2014. Treatment and control areas were randomly designated and comprised of 50 homes per study area. Before cattle treatments, baseline mosquito counts were performed after pyrethrum spray. Cows in the treatment area were administered topical applications of eprinomectin at 0.5 mg/kg once a week for two consecutive weeks. Mosquito collections were performed once each week for two weeks following the eprinomectin treatments. Mosquitoes were first identified morphologically and with molecular confirmation, then screened for sporozoite presence and host blood using PCR-based methods. Results The indoor resting density ofAn. arabiensis was significantly reduced by 38 % in the treatment area compared to the control area at one-week post-treatment (Control mean females per hut = 1.33 95 % CI [1.08, 1.64]; Treatment = 0.79 [0.56, 1.07]). An increase in the indoor resting density ofAnopheles gambiae s.s. andAnopheles funestus s.s. was observed in the treatment area in the absence ofAn. arabiensis. At two weeks post-treatment, the total number of mosquitoes for any species per hut was not significantly different between the treatment and control areas. No change was observed inAn. arabiensis host preference as a result of treatment. Conclusions Systemic drugs may be an important tool by which to supplement existing vector control interventions by significantly impacting outdoor malaria transmission driven byAn. arabiensis through the treatment of cattle.